The Paris 2024 Olympic and Paralympic Games and images of Paris - Alexia Gignon; Marie Delaplace; Felipe Pimenta De Souza (Via@)
In 2024, the Olympic and Paralympic Games will take place in Paris and more broadly in the Île-de-France region. Preparing for this event is a major challenge for the regions involved. According to two questionnaire surveys, one of which was carried out among the population of Île-de-France in 2020 and the other among tourists in 2019, the images of the Olympic Games and the images that these two types of population have of Paris are identified. The different images of Paris for the tourists and the Parisians are analysed, respectively four and three years prior to the Olympic Games. The potential arrival of tourists during the event in 2024 will also be questioned. The results show that the tourists have a better image of the capital than the residents of the Île-de-France region. Nearly 60% of the residents questioned think that it is a good thing or a very good thing that Paris will host the Olympic Games in 2024, while 56% of the tourists know that the Olympic Games will take place in Paris in 2024.